FROM IDEA TO PUBLICATION: CONSTRUCTING A QUALITY RESEARCH PAPER - Djoko Susanto; Adi Masli (LPPM STIE YKPN Yogyakarta, 2025)
This paper provides guidance and best practices for writing a well-structured research paper for publication in peer-reviewed journals. It outlines the research publication process, from idea generation to final acceptance, and offers insights into the key factors editors and reviewers consider when evaluating submissions. More importantly, it shares effective practices to address these critical aspects. We stress the importance of strong writing, focusing on concise language, logical flow, and clear organization. The paper also details recommended approaches for essential sections of a research paper, including the cover letter, abstract, introduction, theory and hypotheses, research design, results, and conclusion. Designed to assist academic researchers at all stages, it helps them avoid common pitfalls and enhance the quality of their submissions. While the guidance draws from the authors' experiences, it serves as a practical framework for navigating the challenges of academic writing, ultimately increasing the likelihood of publication in leading journals and contributing meaningfully to their fields.